2020
DOI: 10.1186/s41927-020-00132-9
|View full text |Cite
|
Sign up to set email alerts
|

Line blot immunoassays in idiopathic inflammatory myopathies: retrospective review of diagnostic accuracy and factors predicting true positive results

Abstract: Background Line blot immunoassays (LIA) for myositis-specific (MSA) and myositis-associated (MAA) autoantibodies have become commercially available. In the largest study of this kind, we evaluated the clinical performance of a widely used LIA for MSAs and MAAs. Methods Adults tested for MSA/MAA by LIA at a tertiary myositis centre (January 2016–July 2018) were identified. According to expert-defined diagnoses, true and false positive rates were calculated for strongly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…is case also highlights the diagnostic dilemma of managing of concurrent myositis specific autoantibodies (MSAs). Both anti-MDA5 and anti-Jo1 Abs are MSA, which are noted to be exclusive in 99.8% of cases and carry 91.9% false positive rate when only weakly positive [11,12]. As such, given anti-MDA5 was only weakly positive, the anti-Jo1 was felt to be the true positive initially, leading a working diagnosis of antisynthetase syndrome with ILD.…”
Section: Discussionmentioning
confidence: 99%
“…is case also highlights the diagnostic dilemma of managing of concurrent myositis specific autoantibodies (MSAs). Both anti-MDA5 and anti-Jo1 Abs are MSA, which are noted to be exclusive in 99.8% of cases and carry 91.9% false positive rate when only weakly positive [11,12]. As such, given anti-MDA5 was only weakly positive, the anti-Jo1 was felt to be the true positive initially, leading a working diagnosis of antisynthetase syndrome with ILD.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, data from different studies were summarized showing varying agreement (from low to high, kappa: PM/Scl, 0.48; Jo-1, 0.52; Mi-2; 0.56; SRP, 0.60; TIF1y, 0.71; PL-12, 0.72; EJ, 0.72; MDA5, 0.75; SAE, 0.79; Ku, 0.83; NXP-2, 0.86; PL7, 0.82). Part of this inter-method variability might be attributed to the subjectivity associated with interpretation [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ] which can be addressed by automated scanning systems [ 11 , 32 ] that allow for a ‘semi-quantitative‘ assessment and thus for the estimation of antibody levels (titers). Due to the lack of correlation between LIA results, IP and IIM phenotypes, Mecoli et al proposed modified cut-offs for the different MSA [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been already demonstrated that multiple testing, whereas increasing efficiency could also increase false-positive results. Several reports described how the agreement between commercial assay and IP may be influenced by the rarity of the autoantibody or by the antigen specificity and no conclusive data are currently available [16][17][18][19][20][21][22][23][24][25][26]44]. In 2019, Fiorentino et al compared results from LB and IP in DM patients, and only a fair concordance was found for NXP2 specificity [26] differently from the moderate concordance shown by a previous study [17].…”
Section: Discussionmentioning
confidence: 99%
“…Historically, these clinical associations have been described when the immunoprecipitation (IP) technique was used for anti-NXP2 detection. Commercial line/dot immunoassays have been released in the last few years; to date, the performance of these tests in IIM is still under discussion [16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%